2010
DOI: 10.12968/jowc.2010.19.1.46093
|View full text |Cite
|
Sign up to set email alerts
|

A hydrocellular foam dressing versus gauze: effects on the healing of rat excisional wounds

Abstract: These results supports the hypothesis that gauze encourages scab formation, which impairs epithelialisation and increases VEGF expression. In contrast, hydrocellular foam dressing accelerates epithelialisation and new vessel formation in granulation tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Dry scabbing delays the epithelialization of wounds (Kunugiza, Tomita, Moritomo, & Yoshikawa, 2010), and epidermal regeneration can be accelerated by the maintenance of a moist wound (Winter, 1962). This finding indicates that topical insulin cream may promote wound healing by accelerating epithelialization.…”
Section: Discussionmentioning
confidence: 92%
“…Dry scabbing delays the epithelialization of wounds (Kunugiza, Tomita, Moritomo, & Yoshikawa, 2010), and epidermal regeneration can be accelerated by the maintenance of a moist wound (Winter, 1962). This finding indicates that topical insulin cream may promote wound healing by accelerating epithelialization.…”
Section: Discussionmentioning
confidence: 92%
“…HCF is particularly suitable for heavily exuding wounds, which require optimal retention of moisture at the surface of the wounded area. 6,[12][13][14][15] Wound fluid contains several cytokines, chemokines, and growth factors, and it has been shown that the components of wound fluid varied depending on the type of dressings used. 9,11 In a past study, HCF-induced moist conditions were reported to be beneficial to the wound healing process by increasing hyaluronan synthesis and decreasing proinflammatory cytokines in the periwound skin.…”
Section: Discussionmentioning
confidence: 99%
“…6,[12][13][14][15] In a previous study, we showed that HCFs were beneficial to wound healing by increasing the gene expression of hyaluronan synthase 3 and peroxisome proliferator-activated receptor-a in the periwound skin. 16 Additionally, we showed that HCF reduced inflammatory cytokine levels in the periwound skin and the granulation tissue.…”
mentioning
confidence: 99%
“…To clarify the mechanisms resposible for the wound-promoting effect of this type of dressing, the other stages of wound healing, such as granulation tissue formation phase, should be addressed. Kunugiza et al [21] reported that the hydrocellular foam dressings accelerated neovascularization in the granulation tissue by enhancing vascular endothelial growth factor. Taken together, this type of dressing has beneficial effects on both granulation tissue and re-epithelialization in the full-thickness wound.…”
Section: Discussionmentioning
confidence: 99%